Bringing Organisations and Systems Back Together: Extending Clark's Entrepreneurial University. (16th February 2017) - Rhoades, Gary; Stensaker, Bjørn
Abstract: Burton R. Clark's 1998 book, Creating Entrepreneurial Universities, has had a major impact on the field of higher education, especially internationally. In this paper, key aspects of Clark's conceptualisation of organisational pathways of transformation are identified, speaking to its theoretical and empirical contributions to higher education studies, policy and practice. In addition, the larger corpus of Clark's work is built on to offer avenues by which considerations of systems analysis and organisational studies can be brought back together to address the strategic challenges and opportunities for individual universities and state as well as national systems of higher education.